Contact between adult children and their divorced parents: Italy in a comparative perspective - Marco Albertini; Chiara Saraceno (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2007)
This paper, based on a Multipurpose survey on a large national sample of Italian households which has made possible to analyse parent-child and grandparent-child dyads, explores the impact of marital instability on relationships with adult children and with grandchildren. As in other countries, the impact is more negative in the case of divorce than in case of widowhood and, in both cases, more negative for men than for women. It affects the threegenerational relationship and is not compensated by stronger horizontal kinship ties. The impact is most negative in the case of contacts, while in the case of material support it is more neutral - and even positive for widowed parents, confirming the strong role played by need in Mediterranean countries in the case of the latter. Not only divorce/separation, also remarriage has a negative impact on intergenerational contacts. And in this case the impact is stronger for women than for men. An exploratory comparison with countries where divorce rates are higher and have a different gender culture suggests that although the impact of marital instability is negative in both cases, its intensity is higher in Italy. These results offer new insight into the working of 'strong family ties'. These ties, particularly in the case of men, are more vulnerable to the dissolution of marital bonds than in countries with 'weak family ties'. Finally, family ties are strongly mediated and constructed by women and through relationships between women. When a mother is no longer present alongside the father, even in the case of widowhood, fathers and grandfathers risk weakening the intergenerational link.
Keywords: 300